THE INNOVATIVE DIRECTIONS OF DEVELOPMENT OF THE STATE TAX MANAGEMENT FOR ENSURING SUSTAINABLE GLOBAL DEVELOPMENT OF THE RUSSIAN FEDERATION - T. Kulagovskaya; E. Bilous (Вестник Северо-Кавказского федерального университета)
In article need of transformations and definition of new approaches to implementation of the state tax management is proved. As the main priority objectives of tax management by authors are offered elimination of poverty in certain territorial subjects of the Russian Federation and reduction of level of differentiation of income of the population. The following innovative instruments of tax management: a free tax minimum (creation of threshold level of income during which lower-income strata will be exempted from payment of taxes, will allow to minimize loading) and also tax benefits are developed. As a result of realization of the directions offered by the author it is obviously possible to level social and economic inequality at the mesolevel.